(untitled) (Mongolian Journal of Arts and Culture, 2025)
This study explores the cognitive construction of tribal seals based on archaeological findings, examining their graphic forms, proportional dimensions, ratios, and aesthetic principles. It also presents a methodology for executing these designs through graphic techniques, highlighting how these elements can be reconstructed and interpreted in a modern context. The external form and internal symbolic system of tribal seals reflect the nomadic mindset and cognitive heritage. The origins and development of the primary symbols are illustrated through a schematic representation. This study provides an understanding of the meaning, symbolism, and transformation system of tribal seals, offering opportunities to learn from cultural heritage and apply this knowledge in graphic design, creative industries education, and research. Therefore, research in this field can serve as an important educational resource for future designers, researchers, and enthusiasts. Овгийн тамганы танин мэдэхүйн конструкци, тиг хэмжээг шинжих нь (Aрхеологийн олдворын жишээн дээр) Хураангуй: Археологийн олдворуудад суурилан овгийн тамганы танин мэдэхүйн конструкци, тэдгээрийн дүрслэл хэлбэр, тиг хэмжээс, харьцаа, гоо зүйн хэм хэмжээний үндсийг судлан, график үйлдлээр хэрхэн гүйцэтгэхийг танилцуулж байна. Овгийн тамганы гадаад хэлбэр, дотоод бэлгэдлийн систем нь нүүдэлчдийн сэтгэлгээ, танин мэдэхүйн өвийн илэрхийлэл тул язгуур дүрсний үүсэл, хөгжлийн зураглалыг схемчлэн харуулсан. Энэхүү судалгаа нь овгийн тамганы утга агуулга, бэлгэдэл, хувирлын тогтолцоог ойлгож, соёлын өвөөс суралцах, график дизайн болон бүтээлч үйлдвэрлэлийн сургалт, судалгаанд ашиглах боломжийг олгож байна. Иймд энэ чиглэлийн судалгаа нь ирээдүйн дизайнер, судлаач, сонирхогчдод зориулсан боловсролын чухал эх сурвалж болно. Түлхүүр үгс: конструктив, харьцаа, гоо сайхан, төгс төгөлдөр